âKORUPSI SEJARAHâ DALAM ISLAM - Edi Susanto, Edi Susanto (STAIN PAMEKASAN, 2012)
AbstractThis article tries to show that the internal conflicts amongÂ the ummah have broken sinceÂ theÂ Â earlyÂ periodÂ of Islam. The critical study of early Islamic periodÂ to uncover the historical distortions was regarded dangerousÂ and painful .Â A critical study ofÂ this early period will give us a new description of this period based on a strong data; and this critical history leads us to realize that such critical study will not violate the sacredness of Islam..Kata-kata kuncikorupsi sejarah, al-Khulafaâ al-Rasyidun, Dinasti Umayah, Dinasti Abbasiyah